2020
DOI: 10.1111/ijcp.13758
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastro‐oesophageal reflux symptoms: An Italian cross‐sectional survey focusing on knowledge and attitudes towards lifestyle and nutrition

Abstract: Introduction The gastro‐oesophageal reflux disease (GERD) is a public health issue for its prevalence and association with low life quality and substantial costs. Since most of Italian data refer to over a decade ago, the aim was to provide an updated estimate of GERD symptoms prevalence. Knowledge about appropriate nutrition and behaviours in presence of GERD was assessed. Predictors for symptoms presence and knowledge were explored. Methods This study was an online cross‐sectional survey that investigated so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…Finally, 33 studies were deemed eligible for data extraction and inclusion in this systematic review and meta-analysis. 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 Among these, data from 22 articles conformed to the definition of GERD in the context of the current study. 30 , 31 , 33 , 34 , 36 , 40 , 41 , 42 , 43 , 44 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 A flowchart illustrating the study selection process is shown in Fig.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…Finally, 33 studies were deemed eligible for data extraction and inclusion in this systematic review and meta-analysis. 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 Among these, data from 22 articles conformed to the definition of GERD in the context of the current study. 30 , 31 , 33 , 34 , 36 , 40 , 41 , 42 , 43 , 44 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 A flowchart illustrating the study selection process is shown in Fig.…”
Section: Resultsmentioning
confidence: 62%
“…Two studies adopted a case-control design, 34 , 51 4 studies adopted a cohort study design, 29 , 46 , 47 , 61 and the remaining studies were cross-sectional. 30 , 31 , 32 , 33 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 48 , 49 , 50 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 The sample sizes of the individual studies ranged from 211 to 50,001, with a total of 66,098 cases of symptomatic GER (including 14,192 cases of GERD) and 167,855 participants across all included studies. In terms of GERD diagnosis, 4 studies relied on physician diagnosis, 34 , 40 , 50 , 51 5 studies used the Montreal definition, 41 , 43 , 44 , 52 , 53 and 13 studies employed authoritative questionnaires for diagnosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, many of these procedures (such as endoscopy) were invasive or discomforting for patients, and therefore probably prescribed only if strictly necessary. Indeed, although data on prevalence of GERD were generally scanty and showed a high uncertainty and variability—ranging from less than 20% up to 28% - due to the lack of a standardized definition and of a diagnostic gold standard for this disorder, we cannot exclude an underestimation of GERD in our population of older people ( Valle et al, 1999 ; Zagari et al, 2008 ; Tosetti and Nanni, 2017 ; Eusebi et al, 2018 ; Bert et al, 2021 ). Also, the Global Burden of disease (GBD) included Italy among the countries with highest prevalence of GERD and stated how it increase with age showing a peak among those aged 75–79 years ( GBD 2017 Gastro-oesophageal Reflux Disease Collaborators, 2020 ).…”
Section: Discussionmentioning
confidence: 91%